2020
DOI: 10.3892/mmr.2020.11266
|View full text |Cite
|
Sign up to set email alerts
|

Statin rosuvastatin inhibits apoptosis of human coronary artery endothelial cells through upregulation of the JAK2/STAT3 signaling pathway

Abstract: The purpose of the present study was to explore the potential molecular signaling pathway mediated by the statin rosuvastatin in cultured human coronary artery endothelial cells (Hcaecs) induced by cocl 2. cocl 2 was used to induce the apoptosis of Hcaecs. Myocardial infarction rats were established and received statin or PBS treatment. reverse transcription-quantitative Pcr, western blotting, eliSa, Tunel assay and immunohistochemistry were used to analyze the role of statin treatment. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The cardiac tissue regenerative potential of ROSU was assessed by subcutaneously implanting, right after LAD ligation procedure, osmotic mini-pumps to systemically release BrdU in order to label and track new cardiac cell formation [11]. Twenty-eight days after LAD ligation, in agreement with previous data on statins effects on post-MI myocardial remodeling [35], ROSU significantly decreased infarct scar size by ~30% (24 ± 4% vs. 33 ± 4% in CTRL untreated MI rats, p = 0,0002), preventing reactive cardiomyocyte hypertrophy (246 ± 23 µm 2 vs. 384 ± 45 µm 2 in CTRL untreated MI rats, p < 0.0001) and reducing by ~80% cardiomyocyte apoptosis (0.11 ± 0.05% vs. 0.47 ± 0.24% in CTRL untreated MI rats, p = 0,0004) ( Figure 4A-F). The latter beneficial anatomical and tissue effects of ROSU on post-MI remodeling ensued in decreased LV end-diastolic (6.01 ± 0.12 mm vs. 6.35 ± 0.16 mm, p = 0.0082) and end-systolic (4.05 ± 0.25 mm vs. 4.97 ± 0.27 mm, p < 0.0001) dimensions (Figure 2.4G) when compared to untreated MI control rats, suggesting a more pronounced effects of ROSU on systolic than diastolic LV function.…”
Section: Hmg-coa Reductase Inhibitors Increase Csc Number and New Myosupporting
confidence: 72%
“…The cardiac tissue regenerative potential of ROSU was assessed by subcutaneously implanting, right after LAD ligation procedure, osmotic mini-pumps to systemically release BrdU in order to label and track new cardiac cell formation [11]. Twenty-eight days after LAD ligation, in agreement with previous data on statins effects on post-MI myocardial remodeling [35], ROSU significantly decreased infarct scar size by ~30% (24 ± 4% vs. 33 ± 4% in CTRL untreated MI rats, p = 0,0002), preventing reactive cardiomyocyte hypertrophy (246 ± 23 µm 2 vs. 384 ± 45 µm 2 in CTRL untreated MI rats, p < 0.0001) and reducing by ~80% cardiomyocyte apoptosis (0.11 ± 0.05% vs. 0.47 ± 0.24% in CTRL untreated MI rats, p = 0,0004) ( Figure 4A-F). The latter beneficial anatomical and tissue effects of ROSU on post-MI remodeling ensued in decreased LV end-diastolic (6.01 ± 0.12 mm vs. 6.35 ± 0.16 mm, p = 0.0082) and end-systolic (4.05 ± 0.25 mm vs. 4.97 ± 0.27 mm, p < 0.0001) dimensions (Figure 2.4G) when compared to untreated MI control rats, suggesting a more pronounced effects of ROSU on systolic than diastolic LV function.…”
Section: Hmg-coa Reductase Inhibitors Increase Csc Number and New Myosupporting
confidence: 72%
“…Lipid-lowering therapies, including 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors (i.e., statins) and proprotein convertase subtilisin/kexin type 9 inhibitors, reduce circulating levels of LDL-cholesterol and thus oxLDL in the vessel wall, and decrease the incidence of severe events in CVD ( Silverman et al, 2016 ; Mach et al, 2020 ), although these agents are not sufficient to prevent plaque formation ( Tran-Dinh et al, 2013 ; Moss and Ramji, 2016 ). Moreover, a spectrum of anti-atherogenic effects of statins on the endothelium has been previously discussed in detail ( Xu et al, 2021 ), and includes reduced inflammation through NF-κB blockade ( Greenwood and Mason, 2007 ), inhibition of EC apoptosis via Janus kinase 2/signal transducer and activator of transcription 3 signaling ( Wang K. et al, 2020 ), protection against EndMT via Kruppel-like factor 4/miR-483 ( He et al, 2017 ), epigenetic modulation of ECs through histone modification ( Mohammadzadeh et al, 2020 ), and increased NO production via hydrogen sulfide and eNOS ( Citi et al, 2021 ; Xu et al, 2021 ). Notably, the statin-mediated mechanisms that contribute to elevated eNOS activity include increased eNOS transcription via KLF2 ( Parmar et al, 2005 ), improved eNOS mRNA stability via polyadenylation ( Kosmidou et al, 2007 ), and increased eNOS phosphorylation via phosphatidylinositol 3-kinase/Akt signaling ( Kureishi et al, 2000 ).…”
Section: The Vascular Endothelium As An Emerging Therapeutic Target For Atherosclerosismentioning
confidence: 99%
“…According to this, endothelial STAT3 may have an important role in the protection versus IRI; for example, in mouse model of IR, the ablation of endothelial STAT3 led to a decrease of cardiac function supported by increased inflammation and worsening of capillary integrity [ 221 ]. Other authors demonstrated that in hypoxic human coronary artery endothelial cells, the treatment with statin rosuvastatin improved cell survival through the JAK/STAT3 pathway [ 218 ].…”
Section: Some More Considerations On Mitochondrial Stat3 In Iri and Cardioprotectionmentioning
confidence: 99%